THE ROLE OF SUSTAINABLE TOURISM ACTIVITY ON SUPPORTING PROTECTED NATURAL AREAS. TENDENCIES AND ESTIMATES FOR EUROPEAN COUNTRIES - Gabriela Stanciulescu; Emilia Titan; Daniela Todose; Mihaela Covrig (European Regional Science Association (ERSA), 2010)
The protected natural areas, by their aesthetic, recreational, educational and scientific valences, represent extremely attractive tourist destinations, some of them unique at international level. Their touristic exploitation has different forms from a country to another, from a type of protected area to another. In this paper, the analysis performed point out that the exploitation of natural areas by tourism has different forms, according to their extension, their landscape complexity, their structure and dynamics of the environment components. The touristic theory identifies a series of tourist forms associated to the environment preservation, such as: tourism in natural areas, ecotourism, adventure tourism, tourism in wilderness, camping. As a conclusion, we can say that the protected areas have become more and more a part of tourism, being appreciated as they represent an environment less affected by the human pressure. Presently, they generate a new form of tourism called tourism in protected areas, requiring special care on behalf of the governments in order not to aggravate the impact of tourism on the local environment and cultures.
Keywords: 330; the protected areas; tourism in natural areas; ecotourism; national park